Overseeding Florida Lawns for Winter Color - Laurie E. Trenholm; J. Bryan Unruh (EDIS)
Revised! ENH-14, a 3-page illustrated directory by L.E. Trenholm and J. Bryan Unruh, describes this practice used to provide green winter turf color for Florida lawns — selecting ryegrasses, timing, seedbed preparation, dethatching, seeding, watering, maintenance, and reestablishing permanent grass. Published by the UF Department of Environmental Horticulture, November 2007.